KOMPOSISI pH, SUSUT MASAK DAN DAYA IKAT AIR PADA BERBAGAI JENIS UMUR DAN JENIS OTOT YANG BERBEDA PADA SAPI BALI - Windy Melinda; Khasrad Khasrad; Jaswandi Jaswandi (Wahana Peternakan, 2023)
This study aims to examine the composition of the pH, cooking loss and water holding capacity of Bali cattle, at different ages and muscle locations. The locations of the muscles observed were the Longissimus dorsi (LD), Pectoralis superficialis (PS), Semitendinosus (ST) and Triceps Brachii (TB) muscles. Cattle aged 1-1.5 years and 3.5-4 years with moderate body condition, 250 g of each sample was taken for every 6 Bali cattle. This study used a 4x2x3 factorial design with a total of 24 experimental units, in a randomized block design (RBD), factor A was muscle type (A1 (LD), A2 (PS), A3 (ST), and A4 (TB)). Factor B is age (B1 aged 1-1.5 years and B2 aged 3.5-4 years). The treatment showed a significant effect, so further tests were carried out using the Duncan Multiple Range Test (DMRT) and how to analyze the data using SPSS. The variables measured were pH, cooking losses and water holding capacity. The research data was processed using analysis of variation (ANOVA). The results of this study concluded that there was no interaction between the type of muscle and the age of the cattle in the meat quality test on pH, cooking loss and water holding capacity of Bali beef. Muscle type has no effect on pH, cooking loss and water holding capacity of Bali beef. Age greatly influences the pH of Bali beef and affects the water holding capacity of Bali beef, but has no effect on cooking loss of Bali beef. Keywords: Water Holding Capacity, Muscle Type, Fatty Acid Composition, Bali Cattle, Cooking Loss, Age.